Le dandy, maître de l’art de plaire en déplaisant - Kociubińska, Edyta (Romanica Silesiana, 2021)
According to Jules Barbey d’Aurevilly, the obligation of every dandy is to become a true master in the art of pleasing by displeasing. His words, his tricks, his intrigues will give birth to the stereotype of the dandy conveyed by his contemporaries throughout the 19th century. By referring to the critical texts of the time and modern critical texts, we will attempt to review the main roles of a dandy: a master of elegance, idle master, misogynist master, impassive master, and finally, insolent master. The paper aims to prove that hidden behind the mask of the original eccentric is a rebel protecting his individuality against the surrounding mediocrity.